The Relationship Between Teacher Competence and Student Satisfaction in a State Religious Secondary School in Pahang - Mohd Syafiq Zainuddin; Mazni Muhammad (Universitas Negeri Padang, 2025)
This study investigates the relationship between teacher competence and student satisfaction in religious secondary schools. The primary aim is to determine how various dimensions of teacher competence influence students’ overall satisfaction with the learning experience. A quantitative research design was employed, using structured questionnaires administered to a sample of Form 4 and Form 5 students in selected religious secondary schools in Pahang, Malaysia. The data were analyzed using descriptive statistics, Pearson correlation, and regression analyses. The results revealed that teacher competence particularly in professionalism and content mastery has a strong and statistically significant positive correlation with student satisfaction. Linear regression analysis showed that teacher competence accounts for over 50% of the variation in student satisfaction levels. While the general level of teacher competence was rated as high, the integration of technology in teaching was found to be only moderate. This highlights a need for improved digital literacy among teachers. The study concludes by recommending continuous professional development focused on strengthening teachers’ professionalism, enhancing subject matter expertise, and advancing the integration of educational technology. Support from school leadership and educational policymakers is essential to sustain teacher effectiveness and address the evolving needs of 21st-century education.